Logika Hukum Dan Terobosan Hukum Melalui Legal Reasoning - Ni Luh Putu Vera; Nurun Ainuddin (Jatiswara, 2016)
This study aims to assess the role of legal logic in interpreting the law to achieve a fairer legal process law enforcement and beneficial to society. To obtain the materials needed, this research uses normative research approach to the laws (statute aproach). The results showed Logic law or legal reasoning as a method or system in order to process law enforcement or legal decision making based on the interpretation of the law due to the vagueness of the law went so well that the purpose of the law to achieve legal certainty, fairness and expediency can be achieved. Decision making legal and law enforcement done arbitrarily, not through rationalization correct and did not use a coherent legal interpretation, will make a breakthrough law will be the law of accident.